Bananas and plantains - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Bananas and plantains by J C Robinson 1995 256pp price UKL19.95 ISBN 0 85198 9853